A HYBRID PUSH/PULL SYSTEM IN AN SME BAKERY IN JOHANNESBURG - Masanabo, F.I.; Chatur, Sabrina (The South African Journal of Industrial Engineering, 2023)
Bakery X is a small business in Johannesburg, South Africa that produces baked goods and sells these directly to the end customer. Bakery X has difficulties meeting customer demand for fat cakes during the peak hours of 06:00 to 10:00 and 12:00 to 14:00. Interviews were conducted with employees to identify the production and demand management practices at Bakery X in order to evaluate improvement opportunities. The two main bottlenecks that were identified were a policy bottleneck (dough rising process) and a communication bottleneck. In the current production system, work is released on the basis of perceived demand and not real demand, which has resulted in shortages and the formation of long queues. A hybrid push/pull production system is proposed for implementation to help to eliminate the bottlenecks in the production process, using a Kanban to smooth out the flow and so deliver value to the customer and to Bakery X.